Gastrografin Enemas for Treatment of Distal Intestinal Obstruction Syndrome in Children and Adults with Cystic Fibrosis - Mahmoud Zahra; Carla Frederick; Richard Thomas; Vaseem Iqbal; Drucy Borowitz (Journal of Pharmacy and Nutrition Sciences, 2014)
Background: Distal intestinal obstruction syndrome (DIOS) presents in both children and adults with cystic fibrosis (CF). When DIOS is characterized by bilious vomiting or when washout therapy with polyethylene glycol has failed, radio-opaque hypertonic enema (ROHE) is recommended as the next therapeutic option. Techniques for use of ROHE in infants with meconium ileus are described in the literature but have not been reported for children and adults with DIOS. Methods: We described the technique, volume, and results of Gastrografin enema usage for DIOS in children and adults with CF at our institution between 2006 and 2011. We reviewed the incidence of DIOS reported to the CF Foundation Patient Registry (CFFPR) between 2001 and 2011 Results: The mean amount of dilute Gastrografin used was 1220ml or 31 ml/kg, (range 240 - 3500ml; 19 – 59 ml/kg). Three patients had incomplete resolution after an initial enema and underwent repeat enemas on consecutive days. The incidence of DIOS in the CFFPR increased from 223 to 498 cases in children <18 years and 380 to 813 cases in adults >18 years over the ten year period studied. Conclusions: Large volume radio-opaque hypertonic enemas can resolve episodes of acute DIOS and can be repeated on subsequent days if needed, without complications. The incidence of DIOS reported to the United States CF Foundation Patient Registry has increased in both children and adults over the past decade.